Efficacy of a Single-Agent Ts1 (Tegafur, Gimeracil, and Oteracil) in Recurrent Gastric Cancer after Progression from Previous Oxaliplatin, Irinotecan, and Anti-Her2 Targeted Therapy: A Case Report - Zapanta, John Bryle J.; Gorospe, Charity Viado (Asian Pacific Journal of Cancer Care, 2025)
Background: Gastric cancer ranks fourth globally in cancer-related deaths, with advanced cases having a median survival of less than 12 months. Timely surgery improves survival for localized cancer, but advanced and recurring cases have low survival rates. Treatment options include 5-fluorouracil (5-FU), but TS-1, a modified form of 5-FU, shows promise. Two Japanese trials found TS-1 effective in advanced gastric cancer, with response rates of 44% and 49%, and survival periods of 207 and 250 days. TS-1 has fewer adverse effects than 5-FU. This case report demonstrates TS1’s efficacy as a second-line treatment for recurrent gastric cancer post-previous therapies. Methods: The case involves a 44-year-old Filipino woman with a 2-month history of upper GI symptoms. Results: This case initially presented with symptoms of easy fatigability, epigastric pain, and anemia. Gastroscopy revealed gastric adenocarcinoma, leading to radical subtotal gastrectomy and adjuvant chemotherapy with Epirubicin, oxaliplatin, and capecitabine. She achieved a complete response for nine months until a left pelvoabdominal mass was discovered and surgically removed, revealing recurrent metastatic adenocarcinoma. Treatment shifted to docetaxel, irinotecan, and Trastuzumab due to HER2neu positivity, followed by maintenance therapy with Trastuzumab plus capecitabine. In December 2022, the patient experienced epigastric pain, prompting imaging revealing a stomach mass. Despite local therapy with radiation, gastrointestinal metastasis occurred, requiring TS1 as second-line treatment. The patient remained stable for nine months until presenting with jaundice in December 2023. Imaging revealed progressive disease in the stomach, omentum, and pancreas, leading to obstructive jaundice managed with biliary drainage. However, she developed severe pneumonia, intraabdominal infection, acute kidney injury, and electrolyte imbalances, ultimately leading to her demise. Conclusion: The utilization of TS1 as a second-line treatment for gastric cancer can be effective and shows promising results prolonging patients’ progression free survival and overall survival, it underscores ongoing efforts to tackle refractory cases, emphasizing the imperative for continuous research and innovation in the field.